Bending behaviour of sandwich panels of vegetal fabric reinforced cementitious matrix: Experimental test and numerical simulation. (18th July 2022) - Mercedes, Luis; Bernat-Maso, Ernest; Martínez, Borja
Highlights: Incorporation of novel solutions of vegetal fabrics and connectors to the FRCM composites as skins of sandwich panels. Bending behavior of sandwich panels with vegetal FRCM. Development of effective composite action of sandwich panel with vegetal FRCM. Numerical models adjusted and validated from experimental results. Abstract: Sandwich panels represent a lightweight solution with additional properties as insulation compared to traditional solutions used for building enclosures. In this study, a technology based on vegetal FRCM (fabric reinforced cementitious matrix) provides an economical, sustainable and competitive solution. The research introduces a composite design made of different vegetal fabrics (hemp and sisal) and mortar as skins of the sandwich and a core of extruded polystyrene. Both composite skins were connected with different types of connectors including vegetal designs. An experimental campaign of sandwich panels included four-point bending tests and a later development of numerical models capable of reproducing the experimental results. The results obtained show that the use of vegetal fabrics and connectors were as competitive for the development of effective composite action as synthetic fabrics (glass fiber).